Managing teaching and learning situations at the tertiary level: a qualitative case study of the challenges faced by the academic staff at one of the public universities in Malaysia - Nik Abdul Rahman , Nik Suryani (2012)
Teaching at tertiary level involves a complex and diverse work process. Most higher education faculty received their advancement of content knowledge but is seldom given the opportunity to integrate this content knowledge with the teaching pedagogy (Bartlett, 2005, Cambridge, 1999, Kreber 2001). This paper describes challenges faced by teachers at one of the public universities in Malaysia in the management of their classrooms and the strategies they use to cope with them. 85 university teachers responded in writing to questions posed to them. The results of this qualitative study, consisting of content analysis of short essays reveal at least four themes. They are: Management of learning (ML), Sensitivity to Students (SS), Academic Challenge (AC) and Personality Management (PM). The findings suggest that specific modules are to be drawn up in response to those challenges.